Perceptions, pedagogies, and challenges in critical thinking education. A faculty perspective - Sarvary, Mark A.; Schmidt, Christina M. (Frontiers in Education, 2026)
Critical thinking is an essential skill in higher education, vital for students’ academic success and their ability to address complex, real-world problems in the era of AI and misinformation. This study employs both quantitative and qualitative methods to investigate how critical thinking is taught and assessed in undergraduate courses at a research university, with a focus on faculty perceptions and teaching practices in gateway and non-gateway courses. The authors developed and validated a survey to investigate faculty perceptions of teaching critical thinking, utilizing 14 critical thinking skills identified in the literature. Faculty survey responses reveal discrepancies between how critical thinking skills are included in learning outcomes and how they are taught, highlighting the importance of explicit critical thinking training, particularly in gateway courses. Gateway courses show noticeable gaps in students’ perceived preparedness for critical thinking compared to non-gateway courses. The faculty employed many creative active learning techniques and group work to teach critical thinking. Non-graded activities were preferred to assess students’ critical thinking skills. A qualitative survey with the faculty also identified barriers, including student and faculty attitudes, their abilities to learn and teach critical thinking effectively, and a lack of resources, including time and institutional support. The findings highlight the need for explicit but not time-consuming critical thinking instruction, particularly in gateway courses, to help students build a strong intellectual foundation, positioning undergraduates for academic success and preparation for their future careers.